Discharge Readiness and Patient Experience in the Hospital-to-Home Transition After Digestive Surgery - Fernando Dana; Raquel Sebio-García; Rubèn González-Colom; Beatriz Tena; David Capitán; Dulce Momblan; Eva Rivas; Marina Roger; Paula Isern; María Suárez; Adelaida Zabalegui; Graciela Martínez-Pallí Martínez-Pallí (Journal of Clinical Medicine, 2026)
Background/Objectives: Complete postoperative recovery increasingly occurs after hospital discharge, particularly in the context of enhanced recovery after surgery (ERAS) programmes. However, patient-reported experience during the transition from hospital to home after digestive surgery remains poorly characterized. This study aimed to evaluate patient-reported experience and to explore its associations with perceived quality of recovery at discharge, surgical complexity, postoperative complications, and unplanned healthcare utilization. Methods: This study analyzed a prospective observational cohort of 361 adult patients undergoing elective digestive surgery at a tertiary care center. Patient-reported experience was assessed using an ad hoc structured questionnaire administered at discharge and 30 days later, covering discharge readiness, information, expectations, and support needs. Quality of recovery was assessed using the QoR-15 at discharge. Results: At discharge, 71% of patients reported feeling ready for discharge, whereas 41% agreed that they would have needed a longer hospital stay. At 30 days, 87% reported sufficient home-care information, 69% reported that recovery had met their expectations, 35% perceived discharge as premature, and 23% reported need to contact the hospital. Several ST-PREM domains assessed at discharge or during 30-day follow-up were associated with QoR-15 scores at discharge, with differences exceeding the 6-point minimal clinically important difference (MCID). No consistent differences in patient-reported experience were observed according to surgical complexity. Patients with postoperative complications or emergency department attendance reported less favorable recovery-related experience domains. Conclusions: Most patients reported favorable experiences during the hospital-to-home transition. However, a clinically relevant subgroup reported uncertainty, perceived premature discharge, or need for post-discharge support. Combining patient-reported experience measures with QoR-15 may help provide a more comprehensive evaluation of early postoperative recovery.